Advances in functional training : training techniques for coaches, personal trainers and athletes - Boyle, Michael, ....- (Santa Cruz : On Target Publications, 2017)
In the seven years since the publication of his first book, Functional Training for Sports, new understanding of functional anatomy has created a shift in strength coaching. With this new material, coach Boyle presents the continued evolution of functional training as seen by a leader in the strength and conditioning field.
Met een voorwoord van Alwyn Cosgrove en een introductie door Mark Verstegen
Keywords: Krachttraining